Gulliver's travels - Woodside, Martin; Akib, Jamel; Swift, Jonathan, 1667-1745. (New York : Sterling Pub., 2006)
An abridged version of the voyages of an eighteenth-century Englishm an that carry him to such strange places as Lilliput, where people are six inches tall, and Brobdingnag, a land peopled by giants.
Keywords: Voyages and travels -- Fiction; Fantasy